Association of Serum Uric Acid Level with Short Term In-Hospital Mortality In St-Elevation Myocardial Infarction - Ismail, Muhammad; Mahmood, Asad; Zubair Ahmed; Janjua, Ishtiaq Munir; Ul Hassan, Syed Fahad; Naveed, Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the relationship between elevated blood uric acid levels and short-term in-hospital mortality in myocardial infarction with ST-elevation. Study Design: Quasi-experimental. Place and Duration of Study: Combined Military Hospital (CMH), Hyderabad, Pakistan from Aug to Dec 2023. Methodology: A total of 378 (189 in each group) patients were enrolled, and serum uric acid sample was sent for analysis, patients were monitored for seven days after admission. Patients were split into two groups based on their serum uric acid levels: Group A (exposed) and Group B (non-exposed), identical treatment was given to both groups. Baseline investigations were carried out on admission including ECG, blood complete picture, coagulation profile, cardiac enzymes, lipid profile, chest X-ray, renal and liver function tests and troponins. Results: Group A (high serum uric acid, 10%) had a greater mortality rate than Group B (low serum uric acid, 3%) and significant categories with higher death rates were patients with history of smoking (75.0%, p = 0.029), hypertension (77.8%, p = 0.010), BMI ≤ 25 kg/m² (78.6%, p = 0.033), and men (76.5%, p = 0.026). Results point to serum uric acid as a prognostic biomarker, highlighting its function in risk assessment for treatment of ST-Segment Elevation Myocardial Infarction (STEMI). Conclusions: Elevated serum uric acid level was noted to be linked to a higher in-hospital death rate among patients with ST elevation myocardial infarction.